Analysis of economic incentives for managing risk at the farm level in the context of climate change - Barton, David N.; Kakumanu KR; Palanisami K; Tirupathaiah, K. (Macmillan, 2012)
Weather indexed crop insurance has the potential of offering risk management to high-risk populations in poor areas, by lowering transaction costs of managing contracts and payouts, thereby offering affordable insurance even to poor farmers. Lower transaction costs relative to multiperil yield-based insurance, can be achieved through use of local weather data, rather than on-farm crop cutting experiments, that lowers verification costs, while maintaining, or even lowering basic risk.